2001
DOI: 10.1002/1521-4125(200109)24:9<913::aid-ceat913>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Flow Patterns in Rheologically Evolving Model Fluids Produced by Hybrid Dual Mixing Systems

Abstract: The flow patterns produced by two dual mixing systems composed of independently driven impellers were studied. The dual impellers included a turbine rotating at high speed (Rushton or Smith) and a slowly rotating helical ribbon agitator (HR). Visualizations and power input were used to evaluate mixing performance. The influence of the rotational speed ratio on the flow patterns was evaluated. For high shear‐thinning fluids, NT/NHR modifies the flow patterns considerably. Three typical behaviors were found with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…By adding a wall scraping impeller, such as an anchor, to the system consisting of one or more central impellers, due to the synergistic effects of the impellers the flow patterns change significantly [47]. According to Espinosa et al, these flow patterns are a function of the speed ratio of the impellers (𝑅 𝑁 = high speed (central impeller)/low speed (anchor)) [47]. In co-axial configurations (central impeller and anchor), two extreme conditions happen, namely low-speed ratio and high-speed ratio.…”
Section: Flow Patterns In Gas Dispersionmentioning
confidence: 99%
“…By adding a wall scraping impeller, such as an anchor, to the system consisting of one or more central impellers, due to the synergistic effects of the impellers the flow patterns change significantly [47]. According to Espinosa et al, these flow patterns are a function of the speed ratio of the impellers (𝑅 𝑁 = high speed (central impeller)/low speed (anchor)) [47]. In co-axial configurations (central impeller and anchor), two extreme conditions happen, namely low-speed ratio and high-speed ratio.…”
Section: Flow Patterns In Gas Dispersionmentioning
confidence: 99%
“…A few studies have evaluated coaxial mixers for gas-liquid dispersion applications, and scant data is available for gas dispersion in non-Newtonian fluids. Espinosa-Solares et al [121] studied a helical ribbon-Smith turbine coaxial mixer and reported a good gas dispersion in both Newtonian and non-Newtonian fluids based on visual observation. Also, shorter mixing times were reported compared to single impellers [122].…”
Section: Coaxial Mixersmentioning
confidence: 99%
“…Espinosa‐Solares et al [ 15 ] observed effective gas dispersion in both Newtonian and non‐Newtonian fluids using a coaxial mixer comprised of a helical ribbon and a Smith turbine. The high efficiency of coaxial mixers in dispersing gas was further confirmed in aerated mixing systems with viscous Newtonian fluids through numerical simulations and electrical resistance tomography (ERT) measurements.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Therefore, coaxial mixers have been extensively investigated as an effective alternative in increasing the well-mixed regions since their configuration combines a high-speed central impeller and a close clearance impeller rotating at a lower speed. [11][12][13][14] Espinosa-Solares et al [15] observed effective gas dispersion in both Newtonian and non-Newtonian fluids using a coaxial mixer comprised of a helical ribbon and a Smith turbine. The high efficiency of coaxial mixers in dispersing gas was further confirmed in aerated mixing systems with viscous Newtonian fluids through numerical simulations and electrical resistance tomography (ERT) measurements.…”
mentioning
confidence: 99%